Variation of Bio-Activators (EM-4 and Leri Water) in Processing Household Organic Waste into Organic Compost Ready to Use in Gebang Putih Surabaya - Nur Aini Fauziyah; Reva Edra Nugraha; Kindriari Nurma Wahyusi; Mei Syella Kurnia Putri Cahyo; Mohammad Iqbal (Nusantara Science and Technology Proceedings, 2022)
The simple organic waste processing in this journal is a follow-up to the previous activities. By using a concise method that did not take up land, the people of Gebang Putih Village have been able to process simple organic waste into ready-to-use compost. The method used in making ready-to-use compost was to stack brown and green waste in layers and then doused it with two variations of bio-activators, i.e., leri water (rice washing water) and EM4. After the 18th day, the resulting fertilizer showed dry characteristics, odorless, and had a neutral pH. An interesting result in this study was that the compost with the addition of leri water (pH=7) began to decompose on the 9th day. However, in the compost with the addition of EM4, on the 6th day, the compost had decomposed evenly. However, the final results of the compost produced proved that leri water was quite effective as an alternative bio-activator, a substitute for EM4.